Kajian Nilai Moral dan Religius dalam Novel “Cinta dalam Diam” - Nurhaliza Nurhaliza; Dwi Wahyu Candra Dewi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study examines religious values ​​and the concept of patience and sincerity in the novel "Cinta dalam Diam" by Shineeminka. This fictional novel tells the story of household life and conveys moral messages and values ​​of goodness. With a qualitative descriptive approach and content analysis, this study uses the novel Cinta dalam Diam published in 2017 as a primary data source. The results of the analysis show that the religious values ​​contained in the novel include the relationship between humans and God (belief in Allah, prayer, praying, reading the Qur'an, tawakal), the relationship between humans and parents (devotion), the relationship between humans and others (good and bad morals, helping each other, affection), and the relationship between humans and oneself (patience, sincerity, accepting destiny, gratitude, maintaining honor). The main character, Zahra, is described as a person who has extraordinary patience and a sincere nature and is willing to sacrifice. Overall, this novel is full of religious values ​​and strong moral messages, inviting readers to reflect on the meaning of pure, patient, and sacrificial love according to Islamic law, and to become a better and stronger person spiritually.